DEVELOPMENT OF MODULE ASSISTANCE FOR CHILDREN WITH SPECIAL NEEDS FOR ELEMENTARY SCHOOL - Wiwik Tiyani; Iskandar Wiryokusuma; Hari Karyono (Magister Scientiae, 2020)
This study aims to produce a mentoring module for children with special needs. This research is a development research by adapting the ADDIE development model. The results of the development research showed that the development of the mentoring module for children with special needs was categorized as appropriate according to the evaluation conducted by the teacher as well as the validation of the experts namely the material expert and the learning design expert. The development of this module can increase the interest of teachers when teaching dyslexic children and increase learning motivation of dyslexic students. In addition, intensive coordination is needed between schools and parents in dealing with children with special needs in Santa Clara Catholic Elementary School for the development and progress of students. Based on the results of research and development, it is obtained suggestions in the form of hope that this module will become a means of encouragement to prepare mentoring modules for teachers who do not understand the psychological side of children with special needs.